2016
DOI: 10.1016/j.bmcl.2016.07.050
|View full text |Cite
|
Sign up to set email alerts
|

A new class of flavonol-based anti-prostate cancer agents: Design, synthesis, and evaluation in cell models

Abstract: Flavonoids are a large class of polyphenolic compounds ubiquitously distributed in dietary plants with an array of biological activities. Flavonols are a major sub-class of flavonoids featuring a hydroxyl group at C-3. Certain natural flavonols, such as quercetin and fisetin, have been shown by in vitro cell-based and in vivo animal experiments to be potential anti-prostate cancer agents. However, the Achilles' heel of flavonols as drug candidates is their moderate potency and poor pharmacokinetic profiles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Results showed that genistein inhibited PCa cell growth through upregulation of tumor suppressor miR-34a, which directly targets HOX Transcript Antisense RNA (HOTAIR), a lncRNA that regulates key pathways in PCa invasion and metastasis [153]. A few recent studies focused on the interaction between miRNAs and lncRNAs in human cancer cells [154][155][156][157]. HOTAIR can function as a scaffold through binding and directing EZH2 and Lysine (K)-specific demethylase 1A (LSD1) to occupy the same genomic regions.…”
Section: Isoflavonoidsmentioning
confidence: 99%
“…Results showed that genistein inhibited PCa cell growth through upregulation of tumor suppressor miR-34a, which directly targets HOX Transcript Antisense RNA (HOTAIR), a lncRNA that regulates key pathways in PCa invasion and metastasis [153]. A few recent studies focused on the interaction between miRNAs and lncRNAs in human cancer cells [154][155][156][157]. HOTAIR can function as a scaffold through binding and directing EZH2 and Lysine (K)-specific demethylase 1A (LSD1) to occupy the same genomic regions.…”
Section: Isoflavonoidsmentioning
confidence: 99%
“…4,11,18 Trimethoxyflavonol ( 3 ) has been revealed to arrest cell cycle at the G 2 /M phase in murine TRAMP C2 prostate cancer cells, but have no effect on human 22Rv1 cell cycle distribution. 9 No report was available so far on PC-3 cell cycle perturbation activity of trimethoxyflavonol ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…11,1921 Additionally, trimethoxyflavonol ( 3 ) has been reported to induce mouse prostate carcinoma TRAMP C2 cell apoptosis in vitro as detected by annexin V staining, but not in human prostate carcinoma 22Rv1 cells. 9 No apoptosis activation of trimethoxyflavonol ( 3 ) in human androgen-insensitive PC-3 prostate cancer cell line has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies suggest that introduction of one substituent group, especially lengthy and/or bulky group to a phenolic hydroxyl group might be the best strategy for modification of quercetin as anti-prostate cancer agents [20]. Incorporation of an appropriate amino moiety to the 3-OH of 3',4'-dimethoxyflavonol through a three-carbon linker led to the optimal derivative 2 with up to 292-fold increase in potency [21] in three prostate cancer cell lines. Also, modification of 5-OH of 2,3-dehydrosilybin (another group of flavonoids) resulted in an optimal derivative 3 that can consistently inhibit prostate cancer cell proliferation [22].…”
Section: Introductionmentioning
confidence: 99%